Pécs gazdasági helyzete a szerb megszállás idején : 1918-1921 - Kaposi, Zoltán (Közép-Európai Közlemények, 2011)
After the World War I, (from the middle of November 1918) Pécs was occupied by the Yugoslav army. This military occupation deepened the problems of the city, which was already exhausted due to the war. In my study I examine those economic elements which got into crisis. The crucial problem was caused by the supply of the Serbian army, because free products were rarely available on the market. The Yugoslav army paid nothing for the provided goods; therefore, the costs of these were the burden of Pécs. Huge inflation, dropping of real wages and permanently rising unemployment characterized this period. One result of the isolation of Pécs (because of the Serbian army) was the lack of cash, which was solved by the city with the help of issuing emergency paper money. The private sector was suffering severe atrocities. Many plants were completely plundered; others were excised or distrained (sequestrum). The occupation ended in the summer of 1921, when Pécs has become the part of Hungary again.